A design environment for the automated optimisation of low cross-polarisation horn antennas - Van der Walt, Madele (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.